2017
DOI: 10.11114/jets.v5i4.2171
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Preschool Teachers’ Sense of Efficacy: A Case of TRNC

Abstract: Determining the factors that affect teachers' competences has a decisive role in revealing the quality of teaching process. In this context, it is important to identify professional variables affecting the self-efficacy of preschool teachers. For this reason, it is aimed to investigate which professional variables influence preschool teachers' sense of efficacy. In the research, a descriptive research model was adopted. The working group of the study is composed of 191 preschool teachers participating in publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…However, in a review of seven large scale studies, Early and colleagues (2007) found contradictory effects of formal teacher education on quality of ECEC settings. Regarding teacher experience, Guo and team (2011) found that teachers' teaching experience was not a significant predictor of teachers' self-efficacy, while Toran (2017) found a significant relationship between the duration of professional experience and teacher self-efficacy in a study which included 191 preschool teachers. Moreover, consistent with previous research, the current study did not find that the number of children in each classroom was associated with teacher sense of self-efficacy (Toran, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a review of seven large scale studies, Early and colleagues (2007) found contradictory effects of formal teacher education on quality of ECEC settings. Regarding teacher experience, Guo and team (2011) found that teachers' teaching experience was not a significant predictor of teachers' self-efficacy, while Toran (2017) found a significant relationship between the duration of professional experience and teacher self-efficacy in a study which included 191 preschool teachers. Moreover, consistent with previous research, the current study did not find that the number of children in each classroom was associated with teacher sense of self-efficacy (Toran, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Professional development and in-service training can positively influence teacher selfefficacy (Bray-Clark & Bates, 2003;Santiago et al, 2022;Toran et al, 2017). For many educators who do not participate in formal preparation programs, in-service training often overlaps as default preparation for practice (Institute of Medicine & National Research Council, 2015).…”
Section: Teacher Self-efficacymentioning
confidence: 99%
“…Kajian Toran (2017) berkaitan efikasi kendiri guru prasekolah yang menggunakan instrumen TSES telah dapat melihat efikasi guru prasekolah berdasarkan beberapa variabel berkaitan pembangunan profesional yang dikaji. Toran (2017) mendapati latar belakang akademik iaitu berkaitan dengan jenis program guru bergraduasi mempengaruhi tahap efikasi secara signifikan.…”
Section: Sorotan Literaturunclassified